A study on feto-maternal outcome in patients with preterm premature rupture of membranes - Shah, Niki; Patel, Vipul S.; Shaikh, Anisa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Preterm premature rupture of membranes (PPROM) is rupture of fetal membranes prior to labor in pregnancies between 28-37 weeks. PPROM is associated with significant maternal and neonatal morbidity or mortality. The present study was conducted to evaluate risk factor and etiology of PPROM and its fetomaternal effect in tertiary care hospital. Methods: A cross-sectional study was conducted in the department of obstetrics and gynaecology, SMS Hospital, Ahemdabad. From August 2023 to February 2024.The study included 50 pregnant women between 28-37 weeks gestation with PPROM were subjected to detailed history and examination. Each patient was followed till her delivery and fetomaternal outcome was recorded. Results: PPROM is a fair complication of pregnancy. 80% were belongs to 20-29 age, 70% were unbooked, 76% from low SE-class, 68% with gestational age of 34-36 weeks. Vaginal delivery was common 58%. The babies born to mothers with PPROM more in weight of 2-2.5 kg (48%). 34 had no risk factors to develop PPROM. Most common etiology for PPROM infection 16% and malpresentation 10%. Most of the mothers with PPROM had no complications. 17 (34%) babies required NICU admissions for complaints of premturity, respiratory distress, birth asphyxia, and sepsis. RDS was most common neonatal complication. 2 neonatal deaths in this study due to RDS and prematurity. Conclusions: Effective PPROM Mx involves evaluating the risks and advantage of conservative Mx strategies. Whenever possible, Rx should be focused towards prophylactic use of antibiotics and steroids during pregnancy can reduce fetal and mother morbidity and mortality. Termination of pregnancy should be considered at the 1st sign of chorioamnionitis.